2001
DOI: 10.1097/00005768-200104000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic exercise induces moderate acute phase response

Abstract: Two hours after cessation of exercise the neutrophils increased stronger after AN-TS than after SMT (P < 0.01). The peak in the number of premacrophages occurred earlier after SMT (15 min post; P < 0.01 to Co-Day) than after AN-TS (2 h post; P < 0.05 to Co-Day). IL-6 was elevated at 15 min and 2 h after AN-TS (P < 0.01 to SMT and Co-Day) but only slightly 2 h after SMT (P < 0.01 to Co-Day). There were no significant changes in IL-8. CRP was the only elevated parameter 24 h postexercise exclusively after AN-TS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0
5

Year Published

2002
2002
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 15 publications
0
39
0
5
Order By: Relevance
“…Conversely Meyer et al 18 showed a significant increase in CRP 24h following an anaerobic cycling session. It was suggested that athletes/physicians should interpret these elevated levels of CRP as a sign that the inflammatory response has not resolved and thus the athlete should reduce or limit the number of sessions that induce this response.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Conversely Meyer et al 18 showed a significant increase in CRP 24h following an anaerobic cycling session. It was suggested that athletes/physicians should interpret these elevated levels of CRP as a sign that the inflammatory response has not resolved and thus the athlete should reduce or limit the number of sessions that induce this response.…”
Section: Discussionmentioning
confidence: 89%
“…Whilst numerous studies have shown the APP C-reactive protein (CRP) to be significantly elevated following exercise, 18,21,26,27 there still remain a large number of acute phase reactants that have not been thoroughly investigated. Therefore, the aims of this study were firstly to confirm the reported increases in CRP following a prolonged, strenuous bout of exercise, and secondly to monitor alterations in less researched acute phase reactants, up to 3 days after an ultramarathon.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 Likewise, some studies reported that acute strenuous exercise could raise CRP levels. 26, 27 Although we did not evaluate the relation between the extent of weight loss and the intensity of exercise training, the inflammatory stimuli derived from a strenuous exercise might be responsible for the results. The rather increased levels of serum uric acid in group D might possibly be caused by vigorous exercise training.…”
Section: Discussionmentioning
confidence: 98%
“…During intense physical exercise there is release of reactive oxygen species (7) and stimulus to the inflammatory process through the release of cytokines (25) , which may result in increase of the cerulloplasmin concentration (26) , once both the cerulloplasmin synthesis and release in the serum are stimulated by the interleukins 1 and 6 (27) . Nevertheless, it is possible that the increase in cerulloplasmin in response to the interleukins in the physical exercise is also associated with its role as antioxidant (22,26) .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it is possible that the increase in cerulloplasmin in response to the interleukins in the physical exercise is also associated with its role as antioxidant (22,26) . The cerulloplasmin concentration in the present study was sensitive to the serum copper concentration.…”
Section: Discussionmentioning
confidence: 99%